O “ANIMAL ELETRÔNICO”: dilemas do ciberativismo verde - Feldman Marzochi, Samira (Caderno CRH, 2015)
73 Samira<p style="font-size: 13.192px; color: #000000; font-family: verdana,arial; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;">Combinando as principais contribuições teóricas do Estruturalismo, Fenomenologia e Teoria Crítica, este artigo parte do pressuposto de que a vulgarização do termo “rede” tem contribuído para um entendimento apologético de fenômenos contemporâneos relacionados ao tema da política e da comunicação, incluindo-se a prática do “ciberativismo”. No intuito de retirar a carga ideológica do conceito, o artigo pincela as mudanças nas relações entre indivíduo e esfera pública desde a Grécia antiga, passando pela industrialização, até deter-se na modernidade contemporânea. A partir desta contextualização teórica e histórica, foi possível analisar criticamente a correspondência, presente no senso comum, entre “ciberespaço” e esfera pública, “ciberativista” e sujeito político, bem como apontar a virtualização da natureza e das questões ambientais, perpetrada pelas campanhas de organizações não governamentais. Assim, é apresentado o conceito de “animal eletrônico” como alegoria de uma “antipolítica”, da ausência da dimensão política que caracteriza os homens, os distingue entre si e do r eino natural. <p style="font-size: 13.192px; color: #000000; font-family: verdana,arial; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;">Palavras-chave : Cultura Política; Comunicação; Esfera Pública; Ambientalismo; Novas Tecnologias; Desterritorialização. <p style="font-size: 13.192px; color: #000000; font-family: verdana,arial; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;"><span style="color: #000000; font-family: verdana,arial; font-size: 13.192px; font-style: normal; font-variant: normal; font-weight: bold; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; display: inline ! important; float: none; background-color: #ffffff;">The ‘electronic animal’: dilemmas of green cyberactivism Samira Feldman Marzochi <p style="font-size: 13.192px; color: #000000; font-family: verdana,arial; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;">By combining the main theoretical contributions of Structuralism, Phenomenology and Critical Theory, this article starts from the premise that the vulgarization of the term “network” has contributed for an apologetic understanding of contemporary phenomena related to the subjects of politics and comunication, including the practice of “cyberactivism”. In order to remove the ideological load of the concept, this article summarizes the changes in the relationship between individual and the public sphere since the ancient Greece, during the Industrial Revolution and in contemporary modernity. From this theoretical and historical context, it was possible to make a critical analysis of the correlation, present in common sense, between “cyberspace” and the public sphere, “cyberactivist” and political subject, as well as to point out the virtualization of nature and environmental issues, perpetrated by NGO campaigns. Thus, we present the concept of “electronic animal” as an allegory for an “antipolitics”, for the absence of the political dimension that characterizes men and distinguishes them from themselves and the natural domain. <p style="font-size: 13.192px; color: #000000; font-family: verdana,arial; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;">Palavras-chave : Political Culture; Communication; Public Sphere; Environmentalism; New Technologies; Deterritorialization. <p style="font-size: 13.192px; color: #000000; font-family: verdana,arial; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;"><span style="color: #000000; font-family: verdana,arial; font-size: 13.192px; font-style: normal; font-variant: normal; font-weight: bold; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; display: inline ! important; float: none; background-color: #ffffff;">L’animal électronique: dilemmes du cyberactivisme vert Samira Feldman Marzochi <p style="font-size: 13.192px; color: #000000; font-family: verdana,arial; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;">En faisant la combinaison des principales contributions théoriques du Structuralisme, de la Phénoménologie et de la Théorie Critique, cet article part du principe que la vulgarisation du terme “réseau” a contribué à une compréhension apologétique de phénomènes contemporains liés au thème de la politique et de la communication, y compris la pratique du “cyber-activisme”. En vue de retirer ce poids idéologique du concept, l’article dépeint les changements dans les relations entre individu et sphère publique depuis la Grèce antique, en passant par l’industrialisation, pour en arriver à la modernité contemporaine. Partant de ce contexte théorique et historique, il a été possible de faire une analyse critique du lien qui existe, dans le sens commun, entre “cyberespace“ et sphère publique, “cyberactivité”... <p style="font-size: 13.192px; color: #000000; font-family: verdana,arial; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;">Palavras-chave : Culture Politique; Communication; Sphère Publique; Environnementalisme; Nouvelles Technologies; Dé-territorialisation. <p style="font-size: 13.192px; color: #000000; font-family: verdana,arial; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;"><small style="color: #000000; font-family: Verdana,Arial,Helvetica; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;">Publicação Online do Caderno CRH no Scielo: http://www.scielo.br/ccrh<span style="color: #000000; font-family: Verdana,Arial,Helvetica; font-size: 12px; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; float: none; display: inline ! important; background-color: #ffffff;"> <br style="color: #000000; font-family: Verdana,Arial,Helvetica; font-size: 12px; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;" /> <br style="color: #000000; font-family: Verdana,Arial,Helvetica; font-size: 12px; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;" /> <small style="color: #000000; font-family: Verdana,Arial,Helvetica; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;">Publicação Online do Caderno CRH: http://www.cadernocrh.ufba.br<span style="color: #000000; font-family: Verdana,Arial,Helvetica; font-size: 12px; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; display: inline ! important; float: none; background-color: #ffffff;"> <p style="font-size: 13.192px; color: #000000; font-family: verdana,arial; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;"> <p style="font-size: 13.192px; color: #000000; font-family: verdana,arial; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;">